2012
DOI: 10.1007/s10562-012-0790-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective Utilization of the Catalytically Active Phase: NH3 Oxidation Over Unsupported and Supported Co3O4

Abstract: The performance of pellets of unsupported and silica-supported Co 3 O 4 in the ammonia oxidation was investigated as a function of the particle size to investigate the utilization of the catalytically active phase in these materials. The obtained activity in terms of ammonia conversion over the silica-supported Co 3 O 4 is higher compared to the conversion over the unsupported Co 3 O 4 , despite a lower cobalt oxide loading and more severe diffusional limitations. The effectiveness factor for the silicasupport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Fortunately, oxides of transition metals, including Mn, Co, and Cu, also exhibit outstanding catalytic performance for lowtemperature HCHO oxidation. Among these, Co3O4 has been widely investigated as a component of heterogeneous catalysts because of its high performance [12][13][14][15][16][17][18]. Many researchers have found that the catalytic activity of Co3O4 varies depending on the method used to prepare the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, oxides of transition metals, including Mn, Co, and Cu, also exhibit outstanding catalytic performance for lowtemperature HCHO oxidation. Among these, Co3O4 has been widely investigated as a component of heterogeneous catalysts because of its high performance [12][13][14][15][16][17][18]. Many researchers have found that the catalytic activity of Co3O4 varies depending on the method used to prepare the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…A further increase in the ammonia conversion is obtained upon the subsequent decrease in temperature. In order to explore this phenomenon better an unsupported Co 3 O 4 pellet was loaded (which showed significant internal mass transfer limitations 15 ). The ammonia conversion increases with increasing temperature up to 640 1C, after which a decrease in the activity is observed.…”
Section: Resultsmentioning
confidence: 99%
“…13 In industrial operation, Co 3 O 4 as an ammonia oxidation catalyst is typically used in the form of catalyst pellets resulting in severe mass transfer limitations. 15 The use of smaller pellets in conjunction with the high linear velocity typically employed in the ammonia oxidation would result in a high pressure drop. Hence, it is desirable to incorporate the catalytically active component in a structured reactor (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of small Co 3 O 4 crystallites in the silicasupported Co 3 O 4 catalyst resulted in a higher effective utilization of cobalt in NH 3 oxidation mainly due to the higher dispersion. 52 Gang et al 45 also suggested the higher activity of NH 3 oxidation was probably due to the small particle size and better dispersion of copper oxide on the support. Importantly, the ammonia oxidation activity at low temperatures was also related to the dissociative or non-dissociative adsorption ability of oxygen on the catalyst.…”
Section: Discussionmentioning
confidence: 98%